Rodents within the Centre for Thai National Reference Collections (CTNRC), Past, Present and Future - Surachit Waengsothorn; Anan Kenthao; Alice Latinne; Jean-Pierre Hugot (Agriculture and Natural Resources, 2009)
The Centre for Thai National Reference Collections (CTNRC) was officially established in 1965, but animal collections in Thailand had been continuously conducted long before this time. This paper gives an historical review of the main steps leading to the constitution of the current collections under the administration of TISTR, with a focus on the rodent collection, which represents about one fifth of the whole mammal specimens. An inventory of the species and genera represented is given. Statistics representing the sampling effort in the different Thai provinces are given. The paper concludes with considerations on the current and future needs and the means necessary to develop and support the efforts of the CTNRC.